Non-Absorbable Oral Gentamicin Sulphate: Biopharmaceutical and Dosage Form Evaluation - Nwakile Dozie C.; Dozie-Nwakile O.C; Okoye E.I; Umeyor C.E; Uronnachi E.C; Uchendu I.K; Attama A.A; Okore V.C (Sciendo, 2021)
Gentamicin sulphate is an antibiotic belonging to the aminoglycosides and to class III of the Biopharmaceutical Classification System (BCS). Gentamicin sulphate is highly water soluble, but has very low intestinal permeability. The wide use is because of its broad spectrum of activity. In the current study, the suitability of administering gentamicin sulphate orally for local action against susceptible gastrointestinal tract (GIT) bacteria was investigated. The possibility of the drug escaping into the systemic circulation even in the presence of some permeation enhancers was ascertained. Representatives of potential GIT bacteria pathogens were evaluated for their susceptibility to the drug at concentrations obtainable in the GIT using standard microbiological methods. Dose levels that will inhibit these potential bacteria pathogens were also established, as well as the frequency of their administration. Different batches of oral capsules of 250 mg gentamicin sulphate were formulated and their release profiles ascertained using standard methods. The results showed that the selected representatives of the GIT potential pathogenic bacteria were all susceptible to gentamicin sulphate. The drug at its plausible dosage levels of 14.28 mg/kg (1,000 mg/70 kg), 10.71 mg/kg (750 mg/70 kg) and 7.14 mg/kg (500 mg/70 kg) did not cross the mucosal barrier into the systemic circulation even in the presence of some permeation enhancers. The drug's frequency of administration were found to be on 8-hourly bases. Gentamicin sulphate (250 mg) granules formulated with polyethylene glycol (PEG 4000) as granulating aid were quick drying because the granules were not hygroscopic. The formulated gentamicin sulphate capsule batch released enough concentration of the drug that inhibits the test organism within 2 min of dissolution. The above stated doses are acceptable in the dosage form design; it is possible to formulate non-absorbable oral gentamicin sulphate dosage form for local activity in the GIT using existing conventional solid dosage formulating equipment.